2013
DOI: 10.1123/jab.29.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Trunk and Pelvic Kinematics During Prolonged Ergometer Rowing in Adolescents

Abstract: The trunk and pelvis kinematics of 20 healthy male and female adolescent rowers were recorded during an ergometer trial using an electromagnetic tracking system (Fastrak). The kinematics of each drive phase were collected during the 1st and 20th minute, respectively. The mean and range of the kinematics, stroke rate and stroke length were compared between genders and over time. Male rowers postured their pelvis with more posterior tilt and their thoracic spine in more flexion than female rowers (P< .05). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Furthermore, given that spinal kinematics differ between genders and that males appear to be more susceptible to LBP, previously successful interventions should be evaluated in the male population. 18,27,33 The aim of this case study was to investigate whether a CFT intervention could alter the spinal kinematics and reduce the LBP of a male adolescent rower during ergometer rowing.…”
Section: T T Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, given that spinal kinematics differ between genders and that males appear to be more susceptible to LBP, previously successful interventions should be evaluated in the male population. 18,27,33 The aim of this case study was to investigate whether a CFT intervention could alter the spinal kinematics and reduce the LBP of a male adolescent rower during ergometer rowing.…”
Section: T T Discussionmentioning
confidence: 99%
“…During the rowing trial, the rower was requested to row at a very high intensity (17/20 on Borg rating of perceived exertion) at a stroke rate of 22 strokes per minute for a period of 15 minutes. This protocol has been used in previous studies 32,33 and was determined after consultations between the research team and coaches. During the ergometry trial, the rate of perceived exertion 3 and the NPRS 7 were verbally collected at the beginning of every minute of the ergometer trial and also at the end of the 15-minute ergometer trial.…”
Section: Laboratory Testing Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…1). In our study, the majority of the patients were female and recent biomechanical data have demonstrated sex differences in trunk and pelvic kinematics with rowing, which may account for the discrepancy [8].…”
Section: Discussionmentioning
confidence: 71%